EVALUASI PROGRAM PENCEGAHAN DAN PENANGGULANGAN TUBERKULOSIS DI WILAYAH KERJA PUSKESMAS TERISI KABUPATEN INDRAMAYU - Widyastuti, Setyo Dwi (JURNAL KESEHATAN INDRA HUSADA, 2023)
Tuberculosis is an infectious disease caused by infection Mycobacterium tuberculosis bacteria. Discovery of tuberculosis cases in the District Indramayu from 2019 to 2021 shows a declining trend for three year of observation, but the TB cure rate in 2019 was 91.9% decreased when compared to 2020 which was reported as many as 70.8%. In 2021 the number of TB cases in Indramayu Regency will be found as many as 1,647 cases. The implementation of the P2TB program has several obstacles including TB program holders who concurrently serve, reporting from Health Center to the Health Service which is not optimal, counseling from the parties Puskesmas related to the TB program are not optimally carried out, and Supervisors Taking Medicines (PMO) that are not functioning optimally. This research method using qualitative research methods with a case study approach. There were 8 informants in this research. The results of this study show that health promotion activities are still not optimal. Human Resources according to standards, the availability of logistics and funds is sufficient. Recording and reporting is still hampered by the network and mastery of health workers to information systems. The participation of the community has not been carried out thoroughly optimal. In the process of implementing the P2TB program, it shows that Program planning at the Puskesmas is good. Implementation of the P2TB Program carried out by visiting contacts at home with TB sufferers and visits independent practice, and the supervision carried out is optimal. Achievement results This shows that the detection of sufferers has not reached the target set. In 2021 the set target is 175, the achievements are only 51 cases found.